PELATIHAN PEMBUATAN PROMPT AI UNTUK SISWA SMP N 47 MERANGIN - Ichsandi Ichsan; Juanita Hibatullah; Lily Indria; Winda Noviana; Widja Yanto; Reyhan Febriantoni (AbdiMasya | Hira Institute, 2024)
The advancement of artificial intelligence (AI) has created new opportunities within the educational sector; however, the ability to utilize it effectively remains a challenge for many students. This community service program aims to train students from SMP N 47 Merangin in crafting effective AI prompts to enhance their self-directed learning processes. The training session took place on January 13, 2025, involving 30 students from grades 7, 8, and 9. The implementation methods included interactive lectures, demonstrations, and guided practice, spanning a total of four hours. Evaluation results indicated a 40.1% increase in participants' understanding, as evidenced by the comparison of pre-test and post-test scores, with a satisfaction rate of 90%. Participants successfully developed their skills in creating effective prompts across various subjects. Technical challenges, such as internet connectivity and differing baseline abilities among participants, were addressed through adaptive solutions. This program has positively impacted the development of students' digital skills and reinforced technology-based learning in the school environment. Recommendations for future development include expanding the program's scope, increasing the duration of practice sessions, and establishing a continuous mentoring system.